2021
DOI: 10.3390/app11094034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Purple-Colored Wheat Bran Addition on Quality and Antioxidant Property of Bread and Optimization of Bread-Making Conditions

Abstract: Purple-colored wheat bran was blended with flour at different ratios. The dough mixing characteristics of the flour–bran blends and quality characteristics and antioxidant activity of the bread prepared with the blends were investigated. Additionally, response surface methodology (RSM) was used to optimize the formula and processing conditions for the bread prepared with the blend at 30% bran. Solvent retention capacity (SRC), as a quality characteristic of the blends, showed that water absorption and damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The baking time-temperature profile has previously been shown to have an effect on the TAC of breads made with coloured wheat wholemeal [ 12 , 13 , 14 , 15 ]. Previous studies have reported that anthocyanin degradation is lower during high temperature, short time processes than in those processes characterized by a lower baking temperature for a longer time [ 12 , 13 , 14 , 15 ]. This trend was also observed in this study on bread baked at 215 °C and 240 °C ( Table 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The baking time-temperature profile has previously been shown to have an effect on the TAC of breads made with coloured wheat wholemeal [ 12 , 13 , 14 , 15 ]. Previous studies have reported that anthocyanin degradation is lower during high temperature, short time processes than in those processes characterized by a lower baking temperature for a longer time [ 12 , 13 , 14 , 15 ]. This trend was also observed in this study on bread baked at 215 °C and 240 °C ( Table 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanin degradation demonstrates first order kinetics, or reduced thermal stability in isothermal systems [ 15 ]. In non-isothermal systems, decreased exposure to high temperatures reduces anthocyanin degradation [ 12 , 13 , 14 , 15 ]. While the increased temperature would be more damaging to the anthocyanins present in the bread, the faster cooking time lowers anthocyanin exposure to temperature, and therefore this type of baking is more protective of anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the anthocyanin loss during baking cannot be completely prevented, it can be slowed down or controlled by altering the variables of the bread-making process. This may include using high-temperature, short-time baking processes, as well as a dough making process at a low pH [ 39 , 40 ]. For example, the fermentation of purple wheat with Lactiplantibacillus plantarum No.…”
Section: Purple Wheat Productsmentioning
confidence: 99%
“…Therefore, an improvement in the quality of bread made with ‘O-free’ flour is needed to meet consumer preferences. The general method to improve the quality of bakery products is to change the basic ingredient formulations and processing conditions or to add vital wheat gluten as a dough improver [ 19 ]. However, the production of bread made with ‘O-free’ flour with vital wheat gluten is undesirable due to increased allergenicity.…”
Section: Introductionmentioning
confidence: 99%